Ископаемые антропогеновые птицы западных областей Украины - Татаринов, К.А.; Марисова, И.В. (Вестник зоологии, 1971)
In western regions of the Ukraine during 1956—1970 as a result of excavations the
promissing burials of fossil Anthropdgeno'us birds were established. The composition
of Anthropogenous avifauna involving 120 species and 8 genera is presented in the article,
a brief characteristic of 16 main occurrences of fossil avifauna is given. The considerations
are made on genesis of recent fauna of birds from the western Forest-Steppe.